Case report: Low-dose radiation reverses pembrolizumab resistance in melanoma - Fong, Ka Hey Agnes; Ho, Isaac; So, Tsz Him (Frontiers in Oncology, 2025)
Immunotherapy has been the mainstay of the initial systemic treatment for metastatic melanoma regardless of the tumor’s genetic mutation status (Atkins et al., 2022). It is known to offer long-term overall and treatment-free survival benefits, also with generally tolerable side effect profiles. However, upon disease progression on first- and second-line immunotherapy, further systemic treatment options are limited especially for cases without actionable molecular alterations. With emerging evidence suggesting that radiotherapy can enhance the efficacy of immunotherapy via various mechanisms, together with its potential abscopal effect, the possibility of overcoming immunotherapy resistance with radiotherapy is theoretically sound. We report a case of metastatic melanoma which demonstrated a reversal of immunotherapy resistance after the addition of low-dose radiotherapy to progressive tumor. Complete metabolic remission is achieved with durable response observed.